A Novel Self-Tuning Fuzzy Logic Controller Based Induction Motor Drive System: An Experimental Approach - Nabil Salem Yahya Farah, Nabil Salem Yahya Farah; Mat Lazi, Jurifa; Ibrahim, Zulkifilie; Jidin, Auzani; Talib, Md Hairul Nizam; Mohd Shah, Nor Shahida; Abdullah, Qazwan (Institute of Electrical and Electronics Engineers Inc., 2019)
High-performance induction motor (IM) drives require fast dynamic responses, robust to parameter variations, withstand load disturbance, stable control systems, and support easy hardware/software implementation. Fuzzy logic control (FLC) for speed controllers is garnering attention from researchers, since it is proven to produce better results compared with the conventional PI speed controllers. However, fixed parameter FLC experiences performance degradation when the system operates away from the design point or is affected by parameter variations or load disturbances. The purpose of this paper is to design and implement a simple self-tuning fuzzy logic controller (ST-FLC) for IM drives application. The proposed self-tuning mechanism is able to adjust the output scaling factor of the main FLC speed controller by improving the accuracy of the crisp output. The IM drive employed an indirect field-oriented control (IFOC) method fed by a hysteresis current controller (HCC). The fixed parameter FLC for the main speed controller comprises nine rules that are tuned to achieve the best performance. Then, a simple self-tuning mechanism is applied to the main fuzzy logic speed controller. All simulation work was done using Simulink and fuzzy tools in the MATLAB software. The effectiveness of the proposed controller was investigated by conducting a comparative analysis between fixed parameter FLC and ST-FLC in forward and reverse speed operations, with and without load disturbances. Finally, the experimental testing was carried out to validate the simulation results with the aid of a digital signal controller board, dSPACE DS1104, with an induction motor drive system. Based on the results, the ST-FLC showed superior performance in transient and steady-state conditions in terms of various performance measures, such as overshoot, rise time, settling time, and recovery time.